2017
DOI: 10.1186/s12967-017-1267-8
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the survival advantage based on telomere length and serum biomarkers of aging

Abstract: BackgroundThis study aimed to establish a model that estimates the survival advantage at the molecular level based on telomere length and serum biomarkers of aging, to explore clinical significance.MethodsThe study consisted of 100 healthy subjects and 40 type 2 diabetes mellitus patients, 20–90 years of age. Saliva telomere relative length (LnTL) was measured by the quantitative real-time polymerase chain reaction and the serum biochemical parameters, including albumin (ALB), total proteins, total cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The telomere DNA gradually shortens with cell division and is closely related to cell senescence and death. For aged people, telomere length was relatively longer in healthy people; individuals with shorter telomeres may have died before reaching an advanced age, and therefore, samples were unavailable [ 20 , 21 ]. Cawthon and his colleagues [ 22 ] measured telomere length in the blood of 143 individuals aged more than 60 years and found that the longer telomere length was correlated with a higher survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…The telomere DNA gradually shortens with cell division and is closely related to cell senescence and death. For aged people, telomere length was relatively longer in healthy people; individuals with shorter telomeres may have died before reaching an advanced age, and therefore, samples were unavailable [ 20 , 21 ]. Cawthon and his colleagues [ 22 ] measured telomere length in the blood of 143 individuals aged more than 60 years and found that the longer telomere length was correlated with a higher survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation also causes telomere shortening by increasing cell turnover, particularly in peripheral leukocytes. Therefore, the shortening of telomeres is often associated with cellular aging and physical aging 3,6,16,25 .…”
Section: Telomere and Telomerase Activitymentioning
confidence: 99%
“…Aging is a significant and uncontrollable risk factor for death [1,24,25]; therefore, determining the effects of aging on cancers with social development is important. The different contributions of age to mortality from cancers between 2004 and 2015 could also be considered as the change in the effect of other risk factors on cancers with time (social development).…”
Section: Biomed Research Internationalmentioning
confidence: 99%